Efficacy of vancomycin and teicoplanin alone and in combination with streptomycin in experimental, low-level vancomycin-resistant, VanB-type Enterococcus faecalis endocarditis. - Nicolau, D P (1996)
The efficacy of vancomycin (VM) and teicoplanin (TE), alone and in combination with streptomycin (SM), against enterococci that express low-level VanB-type VM resistance was investigated in experimental endocarditis using isogenic strains of Enterococcus faecalis susceptible to glycopeptides and aminoglycosides or inducibly resistant to low levels of VM (MIC = 16 micrograms/ml). VM was significantly less active against the resistant strain than against the susceptible strain, establishing that low-level VanB-type VM resistance can influence therapeutic efficacy. By contrast, TE had equally good activity against both strains. VM or TE combined with SM was synergistic and bactericidal against the resistant strain in vitro. While both combinations were efficient in reducing bacterial density in vivo, TE plus SM was significantly superior to VM plus SM if valve sterilization was considered. These data suggest that despite the presence of low-level VanB-type resistance, combination therapy with a glycopeptide and SM (and presumably other aminoglycosides to which there is not high-level resistance) will nevertheless provide effective bactericidal activity.